Service Design Thinking and Social Innovation Sustainability - Sultan, Reem; Qaed, Fatema (2020 Second International Sustainability and Resilience Conference: Technology and Innovation in Building Designs(51154), 2020)
Social Innovation is one of the key indicators within the sustainable development goals (SDGs). Currently, service Design and its design thinking processes play a significant role in Innovation for businesses; it proved its social innovation impact in many projects building sustainable solutions. This study aims to highlight the value of implementing service design through the design thinking process in finding a sustainable solution for different social issues. Researchers achieved the aim of this study using qualitative methodology, implementing case study analysis as a method, were 28 design students have been asked to redesign missing social experiences during pandemics. These case studies explain how sustainable solutions can be generated via service design through the design thinking processes. The findings of this research highlight the value of implementing service design with its design thinking process to generate sustainable solutions for different social issues, concluding that this process can be taught and applied by designers to change their mindsets from `final outcome' to the concept of `final demand', aligning then with sustainability for social Innovation.
Keywords: Co-création; Durabilité; Entreprise; Innovation sociale; Objectifs de développement durable; Réservé UdeM; Résilience; Service design; Villes

Service Design Thinking and Social Innovation Sustainability - Sultan, Reem; Qaed, Fatema (2020 Second International Sustainability and Resilience Conference: Technology and Innovation in Building Designs(51154), 2020)
Social Innovation is one of the key indicators within the sustainable development goals (SDGs). Currently, service Design and its design thinking processes play a significant role in Innovation for businesses; it proved its social innovation impact in many projects building sustainable solutions. This study aims to highlight the value of implementing service design through the design thinking process in finding a sustainable solution for different social issues. Researchers achieved the aim of this study using qualitative methodology, implementing case study analysis as a method, were 28 design students have been asked to redesign missing social experiences during pandemics. These case studies explain how sustainable solutions can be generated via service design through the design thinking processes. The findings of this research highlight the value of implementing service design with its design thinking process to generate sustainable solutions for different social issues, concluding that this process can be taught and applied by designers to change their mindsets from `final outcome' to the concept of `final demand', aligning then with sustainability for social Innovation.
Keywords: Co-création; Durabilité; Entreprise; Innovation sociale; Objectifs de développement durable; Réservé UdeM; Résilience; Service design; Villes